Water Quality Assessment of Yassıalan Dam Lake (Karadeniz Region, Turkey) by Using Principle Component Analysis and Water Quality Index - Ekrem Mutlu; Naime Arslan; Cem Tokatlı (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: In this research, spatial – temporal variations of water quality in Yassıalan Dam Lake were investigated by determining a total of 28 limnologic parameters and by using Water Quality Index (WQI) and Principle Component (PCA).